PENGARUH STIMULASI MENDENGARKAN LAGU DAN BERNYAYI TERHADAP PERKEMBANGAN BERBAHASA PADA ANAK USIA DINI - Ning Setio Wati (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2018)
Language is one of aspects that needs to be incressed for the development of early childhood. This study aims at determining the effect of listening and singing the songs on language development in early childhood at TPA Permata Bunda Metro. The design of this research is Quasi experiment with Nonequivalent control group pretest - postest design. The data collecting technique used observation sheet with a population of 10 children. The sampling technique was sampling random of 5 children. The normality test used Shapiro wilk. The data analized use Mann Whiney U test. The result shows that the value of Mann Whiney U test on language development with significant value 0.01 (P<0.05), it can be concluded that listening and singing the song activity can influence to language development for early childhood.